Cerebellar repetitive transcranial magnetic stimulation versus propranolol for essential tremor. Issue 3 (17th February 2023) - Lv, Yue; Wang, Mengran; Yang, Juan; Shi, Jin; Xuan, Tingting; Zhang, Junmei; Du, Dandan; Cheng, Jiang; Li, Haining
Abstract: Background: Propranolol, a nonselective beta‐adrenergic blocker, has long been used as one of the standard treatments for essential tremor (ET). Repetitive transcranial magnetic stimulation (rTMS) has also been used for a long time as a substitution therapy for ET patients. Objective: The main aim of this study was to evaluate the antitremor effect of 1‐Hz (low‐frequency) cerebellar rTMS and compare it to the use of propranolol in ET patients. Methods: In this single‐blinded, randomized, controlled pilot study, a total of 38 patients with ET were randomized into two groups. One group ( n  = 20) received 1200 pulses of 1‐Hz rTMS at an intensity of 90% of the resting motor threshold to the bilateral cerebellar region for 10 days. Another group ( n  = 18) received oral propranolol for 30 days. The initial dose was 30 mg/day, which was increased to 60 mg/day after 5 days, then to 90 mg/day on the 11th day, and continued thereafter for 20 days. The Fahn–Tolosa–Marin (FTM) clinical scale was assessed at baseline and at days 5, 10, and 30 to evaluate tremor severity, specific motor tasks, and functional disability. Results: Low‐frequency rTMS of the cerebellum significantly improved tremor severity, specific motor tasks (writing, spiral drawing, and pouring), and FTM total scores on days 10 and 30. Nevertheless, we found no significant difference in functional disability at any point in time ( p  > .05). There were no statistically significant differences in FTM Part A, Part B, Part C scores and total scores of patients in propranolol group on days 5 and 10 compared with before treatment ( p  > .05). However, FTM total scores and FTM Part A, Part B, and Part C scores were significantly improved for patients when the dose of propranolol was 90 mg/day on day 30. Our study showed that there was no statistically significant difference in the total FTM scores and FTM Part A, Part B, and Part C scores between rTMS and propranolol on days 5, 10, and 30 ( p  > .05). Conclusion: We conclude that both cerebellar low‐frequency rTMS and propranolol could be effective treatment options for patients with ET, but it is not clear which method is more effective. Abstract : This paper is the first study to compare the effects of rTMS and medication for ET patients. This will help healthcare providers and ET patients select the best treatment.